Pentingnya Pemberian Edukasi kepada Perawat tentang Discharge Planning - Ismuntania Siregar; Indah Nursanti (LPPM AKPER GITA MATURA ABADI KISARAN, 2026)
Education on how to follow up care after a patient is discharged is crucial to maintaining the level of health achieved during treatment, preventing recurrence of future care. Patient discharge planning can foster collaboration with providers of advanced nursing services. Patient discharge planning can improve knowledge, foster awareness of care management, knowledge of medications, and awareness of danger signs that indicate potential complications. This community service activity was conducted at Sawerigading Regional Hospital, Palopo City, South Sulawesi. The target group was 32 nurses working in the inpatient ward. The results showed that the nurses' knowledge was predominantly good (56.3%), sufficient (31.2%), and inadequate (12.5%). Furthermore, the nurses' attitudes were predominantly positive (65.6%), and a minority (34.4%). Nurses' understanding of discharge planning is crucial to maximize patient discharge preparation and readiness for home care to maintain long-term health.